Impact of Political Expectations on Lima Stock Market Returns - Rodríguez, Gabriel (2012)
This paper analyzes the impact of political expectations on the returns of Peru’s stock market using information pertaining to the the electoral periods of 1995 and 2000. The main variable is a measure of the probability that a candidate will win the elections. Therefore, the hypothesis to be proven is whether the uncertainty of the election results affects Peru’s stock market returns. We use other alternative variables such as the exchange rate, inflation, and terms of trade. The results show that for the first period of the analysis (1995), the probability that the candidate Fujimori would win the elections positively affected stock market returns. On the other hand, for the period of 2000, the above-mentioned variable changed, implying a loss of electoral appeal on thepart of the candidate Fujimori. Furthermore, the evidence of corruption uncovered at the time contributed to an explanation of the result’s importance. The results also show the importance ofother macroeconomic variables in the estimations.